Mass transfer in the electrochemical reduction of palladium(II) from a glycinate electrolyte - Nikitenko, V.N.; Kublanovsky, V.S. (Reports of the National Academy of Sciences of Ukraine, 2018)
The ionic composition of a glycinate electrolyte of palladation in the solution volume and in the near-cathode layer, concentration polarization, and alkalinization of the near-cathode layer are calculated within the framework of the Nernst theory, depending on the density of the polarizing current, ratio of main components, and pH0 in the solution volume. The basic forms of existence of palladium(II) ions and the ligand in the nearcathode layer of a glycinate electrolyte are found. It is shown that the electrochemically active complexes [Pd(gly)2] participate in the transition reaction. The reduction of palladium(II) from a glycinate electrolyte is described by the laws of mixed kinetics. The mechanism of electroreduction of palladium(II) from a glycinate electrolyte is proposed.